THE RELATIONSHIP BETWEEN NUTRITIONAL STATUS AND SLEEP DURATION WITH MENSTRUAL CYCLES IN YOUNG WOMEN AT MUHAMMADIYAH BOARDING SCHOOL MODERN ISLAMIC BOARDING SCHOOLS - Sarni Anggoro; Tantiana Isnaningsih; Ahmad Khamid (Jurnal Delima Harapan, 2023)
Discomfort during menstruation is often experienced by young women and some even feel that they have limitations such as not being able to move too actively. Discomfort problems that arise such as pain to interfere with sleep duration. Adolescence is still a period of growth and development so it requires good nutrition to support it. This study aims to determine the relationship between nutritional status and sleep duration with menstrual cycles in young women at the modern Muhammadiyah Islamic boarding school boarding school. This research is a quantitative research with a cross sectional approach. The population in this study were Santri Modern Islamic Boarding Schools Muhammadiyah Boarding School Pleret Yogyakarta, as many as 46 female adolescents. The sampling technique uses total sampling. Data collection uses a questionnaire that has been tested for validity and reliability with valid and reliable results. The results of this study are that the majority of respondents with normal nutritional status and sleep duration are in the sufficient category. The results of the chi square test showed a significance value of 0.564 and there was no relationship between nutritional status and the menstrual cycle in young women. While the results between sleep duration and menstrual cycles obtained a significance value of 0.023 which means there is a relationship between sleep duration and menstrual cycles in young women. Based on the results, it can be concluded that there is no significant relationship between the relationship between nutritional status and the menstrual cycle. However, the second result stated that there was a relationship between sleep duration and menstrual cycle in young women at the Muhammadiyah Boarding School Pleret Yogyakarta Islamic Boarding School.